Training for journalistic of media in Ukraine: Institute of Journalism of University. Taras Shevchenko (1997-2000) - Valeriy Gaydamaka (Cхід)
The article highlights aspects of journalism training personnel for the mass media in Ukraine by the example of the Institute of Journalism of University. Shevchenko in 1997-2000.